DEVELOPMENT OF LEARNING DEVICES IN AGRICULTURAL CHEMISTRY COURSES IN AGROECOTECHNOLOGY STUDY PROGRAM BASED ON KKNI CURRICULUM - Sandy, Sandy Yudha, S.Pd., M.Pd; Siregar, Nur’ Athiyyah Muyassar (PT Ilmu Inovasi Nusantara, 2023)
Learning tools are one of the important factors influencing the success of learning, especially in higher education. By improving the quality of learning tools, it can make it easier for students to understand the materials including agricultural chemistry learning materials. This study aims to develop learning tools in the form of Semester Learning Plans (RPS) and Student Task Designs (RTM) according to the Indonesian National Qualification Framework (KKNI) curriculum. This development was carried out in the agricultural chemistry course in the Department of Agroecotechnology, Malikussaleh University (Unimal). This study uses a research design for the development of a 4-D model by Thiangarajan, but in this study it only reaches 3 stages, namely the definition stage, the design stage, and the development stage. The validators involved in this research are development experts and material experts. The results of the validation of learning tools obtained that the average value of the two devices was 3.62 (very feasible criteria). This means learning tools are made in accordance with Indonesia's national qualification framework